Integrating Islamic Law and Secular Norms: Tunisia's Code of Personal Status as a Model for Legal Pluralism in Muslim Societies - Yulrizal, Yulrizal; Savitri, Desthia Irsa; Saputra, Romia; Aples, Aples; Azizah, Luthfia Ulfa (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
This study analyzes the forms of integration between Islamic law and secular law in Tunisian family law, the legislative process, and state legal argumentation, and their implications for the character of family law as living law. Employing a comparative-historical approach and doctrinal analysis of the Code of Personal Status (CPS) 1956, its amendments, and the Tunisian Constitution of 2014 through thematic categorization and political-legal analysis. The integration manifests in four typologies—substantive, procedural, transformative, and substitutive—which reconstruct Maliki and Hanafi fiqh norms within a modern positive legal framework. The legislative process involves mobilizing political actors, employing dual legitimation strategies (theological-nationalist), and employing state ijtihad through talfiq, takhyir, and maqashid al-shariah. As living law, the CPS has achieved significant social acceptance and strong constitutional legitimacy despite facing resistance from Islamist groups post-2011. The integration of religious and secular law in Tunisia is not total secularization but rather a contextual synthesis that maintains religious legitimacy within the modern state's framework through continuous negotiation among state authority, religion, and social dynamics.